Anterior resection for rectal cancer in Sweden: validation of a registry-based method to determine long-term stoma outcome. (2nd December 2018) - Holmgren, Klas; Haapamäki, Markku M.; Matthiessen, Peter; Rutegård, Jörgen; Rutegård, Martin
Abstract: Background: A permanent stoma after anterior resection for rectal cancer is common. Nationwide registries provide sufficient power to evaluate factors influencing this phenomenon, but validation is required to ensure the quality of registry-based stoma outcomes. Methods: Patients who underwent anterior resection for rectal cancer in the Northern healthcare region of Sweden between 1 January 2007 and 31 December 2013 were reviewed by medical records and followed until 31 December 2014 with regard to stoma outcome. A registry-based method to determine nationwide long-term stoma outcomes, using data from the National Patient Registry and the Swedish Colorectal Cancer Registry, was developed and internally validated using the chart reviewed reference cohort. Accuracy was evaluated with positive and negative predictive values and Kappa values. Following validation, the stoma outcome in all patients treated with an anterior resection for rectal cancer in Sweden during the study period was estimated. Possible regional differences in determined stoma outcomes between the six Swedish healthcare regions were subsequently evaluated with the χ 2 test. Results: With 312 chart reviewed patients as reference, stoma outcome was accurately predicted through the registry-based method in 299 cases (95.8%), with a positive predictive value of 85.1% (95% CI 75.8%–91.8%), and a negative predictive value of 100.0% (95% CI 98.4%–100.0%), while the Kappa value was 0.89 (95% CI 0.82–0.95). In Sweden, 4768 patients underwent anterior resection during the study period, of which 942 (19.8%) were determined to have a permanent stoma. The stoma rate varied regionally between 17.8–29.2%, to a statistically significant degree ( p = .001). Conclusion: Using data from two national registries to determine long-term stoma outcome after anterior resection for rectal cancer proved to be reliable in comparison to chart review. Permanent stoma prevalence after such surgery remains at a significant level, while stoma outcomes vary substantially between different healthcare regions in Sweden.